2017
DOI: 10.22146/gamaijb.22680
|View full text |Cite
|
Sign up to set email alerts
|

Trust, Commitment and Competitive Advantage in SMEs Export Performance

Abstract: Abstract:The entry of small businesses into international markets has intensified. However, despite the growing presence of small businesses in international markets, studies into their international behavior, particularly regarding the effect of international relationships on international outcomes, remain limited. This study investigates the cross-border relationships of Small and Medium Enterprises (SMEs) by examining the effects of the dimensions of the key relationship on the competitive advantage and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 70 publications
1
25
0
1
Order By: Relevance
“…It is in line with research conducted by (Rose, Kumar, & Pak, 2011)organizational learning has a contribution to organizational commitment. The existence of trust and commitment will affect competitive advantage (Ismail, Alam, & Hamid, 2017), This study is the same as research conducted by (Primiana, 2018)commitment influences competitive advantage. According to (Huber et al, 1991), he proposed three component models of organizational commitment that includes three dimensions, namely: 1) Affective commitment is defined as the emotional attachment of employees to the organization, 2) Continuous commitment refers to individual commitment to the organization because individuals feel costly when out of organizational membership, and 3) Normative Commitment refers to the commitment of individuals to stay with the organization because the feeling of obligation.…”
Section: Organization Learning Theorymentioning
confidence: 92%
“…It is in line with research conducted by (Rose, Kumar, & Pak, 2011)organizational learning has a contribution to organizational commitment. The existence of trust and commitment will affect competitive advantage (Ismail, Alam, & Hamid, 2017), This study is the same as research conducted by (Primiana, 2018)commitment influences competitive advantage. According to (Huber et al, 1991), he proposed three component models of organizational commitment that includes three dimensions, namely: 1) Affective commitment is defined as the emotional attachment of employees to the organization, 2) Continuous commitment refers to individual commitment to the organization because individuals feel costly when out of organizational membership, and 3) Normative Commitment refers to the commitment of individuals to stay with the organization because the feeling of obligation.…”
Section: Organization Learning Theorymentioning
confidence: 92%
“…Using the community as a means to maintain economic sustainability in the tourism sector is a part of the effective marketing strategies that considers the consumer behavior (Handriana and Wisandiko, 2017). Furthermore, Ismail and Alam (2017) showed that trust and commitment were essential in maintaining business, so that social relations became a coping strategy to deal with various possibilities that were detrimental to the business.…”
Section: Contribution Of the Development Of Regional Creative Industrmentioning
confidence: 99%
“…The results of Ismail, Alam, & Roshanti (2017) show that support from leaders and supervisors for the application of new skills and knowledge will encourage individuals to apply them in their work. Research conducted by Michell, Steward, & Bruce (2009) shows that the transfer of new skills into work is determined by the support of the leader.…”
Section: Leader Supportmentioning
confidence: 99%
“…Low-educated employees tend to have higher commitments than highly educated employees; (2) role characteristics, where organizational commitment will tend to be stronger for employees who have enriched jobs and jobs that involve low levels of role conflict and ambiguity; (3) structural characteristics, organizational commitment will be stronger in employees who are in a decentralized organization and in cooperation between work owners where employees are more involved in making organizational decisions; (4) work experience, organizational commitment will be strong for employees with pleasant work experience, such as a positive attitude in a group of people towards others, a feeling that an organization can be relied upon to fulfill its organizational commitment to personnel in it and the feeling that individuals in the organization are which is important for the organization. Ismail et al (2017) states that organizational commitment must be seen strategically for the company. Therefore, many companies spend time, energy, and funds to explore organizational commitments related to their activities.…”
Section: Organizational Commitmentsmentioning
confidence: 99%
See 1 more Smart Citation